Os sentidos do sindicalismo na revista Veja : um estudo em representações sociais - Peroni, Guilherme Gustavo Holz (2015)
Trade union is an organization, which defends the rights and interests of workers. Unionism in Brazil was present at important historical moments of the country, such as in the Vargas coup, the military coup of 1964 and the movement of democratization and